Responses to the Missing and Murdered Indigenous Women and Girls Report Within the Canadian Higher Education Sector: A Scoping Review - Alraja, Abeer; Rieger, Kendra L.; Bourque Bearskin, Mona; Reimer-Kirkham, Sheryl; Astle, Barbara; Lounsbury, Kathleen; Morin, Francine; Victor, Patricia; Seymour, Colleen; Johnson, Shelly; Friesen, Monica; Linton, Janice; et al. (Quality Advancement in Nursing Education / Avancées en formation infirmière, 2026)
Background: In 2019, the Final Report of the National Inquiry into Missing and Murdered Indigenous Women and Girls (MMIWG2S+) was released by the Government of Canada, along with 231 Calls for Justice aimed at putting an end to the horrific violence against Indigenous women, girls, and 2S LGBTQQIA+ people.Purpose: The purpose of this scoping review was to examine scholarly articles that have been published in response to the MMIWG2S+ report/Calls for Justice and responses that are presented on higher education websites in Canada.Method: We searched key databases and online sites for relevant sources and screened texts to confirm eligibility. We included 63 scholarly articles and 94 online sources. We conducted content analysis and an analytical synthesis on the data from the academic articles. The online sources were analyzed with content analysis. The responses to the MMIWG2S+ report were categorized into six themes: illuminating report findings for readers; we must act and this is how; discourses about genocide; seeing the bigger picture; a guiding framework for research and practice; and critique of the report and challenges.Results: Reactions to the calls within the higher education sector have been slow and incomplete. Responses are still in their infancy and need to move from discussion to action. Our findings are timely as they hold academics and educators to account through shedding light on the current discussions and (in)actions surrounding the MMIWG2S+ report within higher education.Conclusion: We advocate for Canadian higher education institutions to prioritize the MMIWG2S+ crisis and involve Indigenous organizations and people in their efforts to respond to the report.